PUSKESMAS LANDASAN ULIN BERDASARKAN KLASTER INTEGRASI LAYANAN PRIMER (ILP) - Difa Najla Ufaira; Prima Widia Wastuty (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
Landasan Ulin Community Health Center in Banjarbaru City requires reconstruction to accommodate a cluster-based health service system in accordance with the Minister of Health Decree Number 2015 of 2023 on Primary Health Service Integration. The architectural problem addressed is how to design a community health center that supports health service clusters based on life cycles by applying the wayfinding concept as a medium for direction coordination and spatial orientation through intuitive elements of zoning, color, materials, and signage. The design results in a building with five cluster zones (Management, Mother and Child, Adult and Elderly, Communicable Disease Control, and Cross-Cluster) featuring simple geometric forms with directed circulation, a wayfinding system through distinctive colors, informative signage, and accessible spatial arrangements. The design integrates functional, aesthetic, and comfort aspects while considering health building standards and strategic site conditions on Jalan A. Yani KM 23, thereby creating an efficient, inclusive, and easily accessible health service environment.